APLIKASI Z-SCORE METHOD DALAM PEMBENTUKAN PORTOFOLIO - Isynuwardhana, Deannes (Jurnal Keuangan dan Perbankan, 2013)
The problem that often occurs in forming portfolio was regarding the selection and weighting the stock wichhad to be included in portfolio. This study attempted to solve the problem by using a simple model, which wasexpected to be applied easily by investors. This was a descriptive research with quantitative approach, andused stocks that was categorized as blue chip in Indonesias stock exchange as a sample. Stock selectionprocess used Z-score method with 6 criteria. There were, price earning ratio, price to book value, debt to equityratio, gross profit margin, return on equity, and stocks historical price. The weighting of each stock inportfolio was then calculated by were used Bodie, Kane, and Markus (2011) approach. The coefficient ofvariation, risk and return of the market used as benchmark to measure portfolio performance. The result showedthat portfolio which formed by Z-score method give higher return than the market. Although the portfolioprovided greater risk, but it was not comparable with the marker return that gave negative results in return.The result suggested that portfolio which was created using the Z-score method could be applied by investorsin Indonesias stock exchange.